Guiding Science and Technology: A Systematic Literature Review on the Role of Philosophy of Science - Tanti Permata Sari; Devi Sylvianica; Tri Emelia Rostari; Dian Lestari; Meri Andani (Yayasan Sembilan Pemuda Indonesia, 2026)
Philosophy of science has a very essential role in directing the development of science and technology. As a discipline that studies the nature, methods, and limitations of science, philosophy of science helps provide epistemological, ontological, and axiological foundations in the development of various scientific fields. This study aims to examine the role of philosophy of science in shaping scientific paradigms and its impact on the development of science and technology through the Systematic Literature Review (SLR) approach. By analyzing various studies published in the last five years, this study found that philosophy of science not only functions as a conceptual framework for the development of science, but also as an ethical guide in the use of technology. The research findings show that a deep understanding of the philosophy of science can improve the integration between technological innovation and human values, resulting in more responsible and sustainable scientific development. Thus, this study emphasizes the urgency of a philosophical approach in ensuring the direction of the development of science and technology that is in line with the needs of society and the principles of ethics and sustainability.